Comparison of Real-Q 2019-nCoV and DaAn Gene 2019-nCoV polymerase chain reaction assays for the detection of SARS-CoV-2 - Marembo, Takudzwa; Chimbunde, Prosper; Chipendo, Tendai; Munemo, Clayton; Manangazira, Portia; Bangure, Donewell (Wiley Open Access, 2022)
Background: Various nucleic acid amplification assays for the diagnosis of SARS-CoV-2 infection have been developed, and there is a need to assess their test performance relative to one another. The aim of this study was to compare the performance characteristics of the Biosewoom Real-Q 2019-nCoV assay targeting the E and RdRP genes to DaAn Gene 2019-nCoV kit targeting the N gene and ORF1ab in the diagnosis of SARS-CoV-2.